2015
DOI: 10.13187/es.2015.13.161
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy and Income Inequality in Pakistan: An ARDL Approach

Abstract: This study is an attempt to capture the impact of fiscal policy on income inequality in Pakistan. It employed Autoregressive Distributed Lag (ARDL) model on annual time series data from 1980 to 2012. The stationarity of data is checked by Augmented Dickey Fuller unit root test. Short-run dynamics are tested by error correction model. Model reliability is tested with the help of the diagnostic tests. Chow test is applied to detect structural breaks and Gregory-Hansen technique is employed as a remedial measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…The results explain that public spending on health and education reduces inequality, while progressive taxation plays a significant role in income distribution. Khan and Hashmi (2015) investigate the fiscal policy impact on income inequality. They suggest that development expenditures may be helpful to reduce inequality in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results explain that public spending on health and education reduces inequality, while progressive taxation plays a significant role in income distribution. Khan and Hashmi (2015) investigate the fiscal policy impact on income inequality. They suggest that development expenditures may be helpful to reduce inequality in Pakistan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They believed that fiscal policy had a temporary effect on growth and income inequality. However, endogenous growth models open new prospects by looking into the role of fiscal policy in affecting income inequality (Khan and Hashmi, 2015). Empirical evidence advocates that the composition of fiscal consolidation is an element of rising income inequality that causes a deteriorating distribution of income.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggested that the government can influence the redistribution of income by using effective fiscal policy. Khan and Hashmi (2015) tried to explore the relationship between fiscal policy and income inequality in Pakistan from 1980 to 2012. Results showed that higher government developmental expenditures and financial growth lead to reduced income inequality, whereas fiscal deficit and urbanization increase it in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…In Pakistan, researchers have linked fiscal decentralisation with economic growth, poverty alleviation, government size and public investment (Kang and Arshad 2012;Hussain et al, 2021;Sohail et al, 2021;Hanif and Chaudhry 2015). However, there is a dearth of empirical evidence which specifically links fiscal deficit (fiscal management, public deficit) and FD.…”
Section: Introductionmentioning
confidence: 99%